If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(2 + -1f) = 1 (2 * f + -1f * f) = 1 (2f + -1f2) = 1 Solving 2f + -1f2 = 1 Solving for variable 'f'. Reorder the terms: -1 + 2f + -1f2 = 1 + -1 Combine like terms: 1 + -1 = 0 -1 + 2f + -1f2 = 0 Factor a trinomial. (-1 + f)(1 + -1f) = 0Subproblem 1
Set the factor '(-1 + f)' equal to zero and attempt to solve: Simplifying -1 + f = 0 Solving -1 + f = 0 Move all terms containing f to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + f = 0 + 1 Combine like terms: -1 + 1 = 0 0 + f = 0 + 1 f = 0 + 1 Combine like terms: 0 + 1 = 1 f = 1 Simplifying f = 1Subproblem 2
Set the factor '(1 + -1f)' equal to zero and attempt to solve: Simplifying 1 + -1f = 0 Solving 1 + -1f = 0 Move all terms containing f to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1f = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1f = 0 + -1 -1f = 0 + -1 Combine like terms: 0 + -1 = -1 -1f = -1 Divide each side by '-1'. f = 1 Simplifying f = 1Solution
f = {1, 1}
| 0.3*x^3+0.2*x^2+0.5*x=0 | | f*(2-f)=0 | | 0.3*x^3+0.2*x^2-0.5*x=0 | | 3x^2-11x=15 | | -15ab+21ab= | | N-6+7h=42 | | 3x^2-x-1=0 | | 8x-14=66 | | 2c+2=6 | | x^3-x^2+x-1=x^2+1 | | .25(4f-3)=0.05(10f-9) | | 2x^2-11x+25=0 | | 6x^2+19xy+10y^2= | | x^2=0.75x | | 3v^3+7v^2-15v-35= | | 8t-2=5t+7 | | 4x=3+2x | | 2.7q-5=6.07 | | 2.7q*5=6.07 | | 1.3t=3.25 | | 6(3x-1)=4(4x-5) | | 5x-(8x+46)=270 | | 27-3w^2= | | 3*(2x-2)=22-x | | 3w^2-27= | | 10.99X+10+2=13.99X | | 10.99X+10=13.99X | | 4x-8=9-2x | | -(10+5x)-2x= | | 30+n=30 | | (20x+180)-(30x+50)=40x-60 | | x^2+79=0 |